IMPROVING STUDENTS GRAMMAR ACCURACY IN WRITING THROUGH CONSCIOUSNESS RAISING APPROACH - Bernadeta Diah Ratih Angguratami (Widya Mandala Surabaya Catholic University, 2018)
Grammar an important aspect of communication because it deals with how people are able to express their ideas or thoughts. It is important to construct words and sentences properly in order to convey the points effectively. As an English teacher in Grade X of a senior high school, the researcher found some problems in the students’ writing that made their writing scores to be not satisfying although they gained high scores in reading. Also, grammatical errors were the major problems in the students’ writing. The research was intended to improve the students’ grammar accuracy in writing through consciousness raising. After implementation, the students’ grammar mistakes decreased from the preliminary study to the Third Cycle, the researcher concluded that consciousness raising approach in a form of discovery learning activity helped the students in improving their written grammar accuracy. Some students also stated that discovery learning activities helped them understand their mistakes in applying the Simple Past Tense.